Analysis of Underwriting Procedures in Minimizing the Occurrence of Surety Bond Claims in the Perspective of Sharia Insurance - Fitrah, Al Tasya; Soemitra, Andri; Gultom, Mitra Sami (Universitas Ibn Khladun Bogor, 2023)
A surety bond is a type of liability to bear the consequences of a non-performance of the principal in a construction contract as a form of guarantee to protect the interests of the oblige or the user of the service in the project drive work. The purpose of this research is to provide information on how an Underwriter performs Underwriting Procedures in minimizing the occurrence of Claims on Surety Bonds in PT. Public Insurance Bumida 1967 Field Branch. The method used by the Miles and Huberman techniques is the collection of data from interviews and literary studies. The results of this research show that the procedure used by underwriters in minimizing the occurrence of claims based on applicable company terms by analysing using the 5C method, conducting training of assurance analysis teams and holding risk monitoring. The claim arises due to the existence of a non-performance, which then obligee formally terminate the employment relationship with the Principal, Obligee will file the claim with the Guarantor Company. In Islamic view, surveillance and risk analysis are permitted, but in this procedure the principle of help is eliminated, the investment of funds of any sector, and the occurrence of gharar, in this agreement is prohibited in the principles of Shariah. On the other hand, underwater purposes to preserve and preserve the authenticity of the treasury.